Development of a synthetic library of humanized nanobodies for targeted IL-6 inhibition - Wang, Lei; Dong, Jiayi; Wu, Chenlu; Yan, Chenyue; Bi, Chong; Xu, Chengnan; Wu, Yiling; Zheng, Wenyun; Ma, Xingyuan (Frontiers in Bioengineering and Biotechnology, 2024)
Interleukin-6 (IL-6) is a cytokine that can bind to IL-6 receptor and induce pleiotropic effects. It serves as a critical biomarker, involved in inflammation amplification, tumor progression, and many other disease developments. Nanobodies, featuring small structure and high affinity, are a powerful and versatile tool in medical diagnostics and therapeutics.Here, based on a scaffold optimized for humanization and stability, we developed a synthetic phage display library that rapidly generated high-affinity and humanized nanobodies, negating the need for animal immunization. Using enhanced green fluorescent protein (eGFP) as a benchmark, we demonstrated that the library produced humanized nanobodies with high function and great intracellular stability. The library was then subjected to screening against IL-6. We identified a standout nanobody, NbL3, which exhibited high affinity (22.16 nM) and stability and significantly inhibited IL-6-enhanced migration on the human breast cancer cell MCF-7 at a relatively low concentration. NbL3's strong blocking activity provides a promising therapeutic alternative for the IL-6-targeted